2022
DOI: 10.1039/d2cb00045h
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis reveals the effect of hairpin loop formation on G-quadruplex structures

Abstract: This work studies the intrinsic fluorescence properties of long-loop G-quadruplexes (G4) with hairpin loop structures, revealing the unique information of G4 provided by intrinsic fluorescence compared to other spectroscopic assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, peripheral nucleobases may be located at loops linking the G-tetrads among them or appear as ending groups . The latter were found to affect the fluorescence properties of G4 along with their topology or the type of the metal cations in their central cavity. , Another important structural characteristic of G4 is their molecularity . They may be formed by folding of a single, guanine-rich, DNA/RNA strand (monomolecular G4) or the association of two, three, or four strands, giving rise to bimolecular, trimolecular, or tetramolecular structures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, peripheral nucleobases may be located at loops linking the G-tetrads among them or appear as ending groups . The latter were found to affect the fluorescence properties of G4 along with their topology or the type of the metal cations in their central cavity. , Another important structural characteristic of G4 is their molecularity . They may be formed by folding of a single, guanine-rich, DNA/RNA strand (monomolecular G4) or the association of two, three, or four strands, giving rise to bimolecular, trimolecular, or tetramolecular structures, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It discusses the reasons for which certain structural parameters (molecularity, topology, peripheral bases, and metal cations in the central cavity) affect, on the one hand, the fluorescence quantum yield Φ fl and the fluorescence spectral shape, and on the other, the photoionization quantum yield Φ i . Although similar questions have been addressed in phenomenological studies carried out by steady-state measurements, [31][32][33][34][35] the knowledge of the underlying primary processes offers a different perspective.…”
Section: Introductionmentioning
confidence: 98%
“…While most rG4s were canonical quadruplex structures (G 3–5 N 1–7 G 3–5 N 1–7 G 3–5 N 1–7 ), about 15% (595) of the rG4s were found to contain longer loops ( n > 7). For those long-loop rG4s, 39% had the potential to form duplex (or hairpin) structures by base pairing within loops, making their 3D structures distinct from simpler G4s. Among the 230 putative hairpin-containing rG4 sequences corresponding to 72 genes (Supplementary File 1), a short RNA sequence from DHX15 mRNA was notable for three reasons. First, DHX15 protein is an RNA helicase involved in mRNA processing and immunity. , It has been reported that DHX15 is overexpressed in and leads to the progression of several cancer types, including prostate cancer, Burkitt lymphoma, and acute myeloid leukemia. Second, as an RNA helicase, the DHX15 protein is difficult to target directly and selectively at the protein level with small molecules due to conserved nucleotide binding sites and complex ATP-dependent and -independent mechanisms. , No chemical inhibitors targeting this helicase have been published, and targeting the structured mRNA of DHX15 presents a potential path forward to targeting this disease-relevant gene that is complementary to targeting the protein itself.…”
mentioning
confidence: 99%